PANDANGAN POSITIF DAN NEGATIF TERHADAP KARYA-KARYA ANTROPOLOGI ISLAM DI INDONESIA - Fajarini, Ulfah (Analisis: Jurnal Studi Keislaman, 2014)
POSITIVE AND NEGATIVE OUTLOOKS IN THE WORKS OF ANTHROPOLOGY  OF ISLAM  IN INDONESIA:  This  article compares the works of Western  and Indonesian  anthropologists who studied Islam in Indonesia as well as to uncover positive and negative western anthropologists insights reflected in their works.To parse this phenomenon, the author examines several academic works  of a number  anthropologists such  as: Clifford  Geertz’s, a pioneer  in understanding  and explaining  the  phenomenon  of Muslims in Indonesia; Anthony Reid’s, the founder of the concept of “nationalist orthodoxy”; Robert Jay’s, who reveal the influence of religion on political schism between the Santri (devout Muslim or Islamist)  and the Abangan (less devout Muslims); along with some other  works such as: Andrew Beatty’s,  John R. Bowen’s, Robert W. Hefner’s, JL Peacock’s, Martin van Bruinessen’s, and Mark R. Woodward’s. Aside from that,  the author  also tries  to uncover the role of Indonesian Islamic anthropologists pioneered by researchers from the Research Center for Religious Life of the Ministry of Religious Affairs.